2021
DOI: 10.3390/technologies9030047
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision Framework for Wheat Disease Identification and Classification Using Jetson GPU Infrastructure

Abstract: Diseases have adverse effects on crop production and yield loss. Various diseases such as leaf rust, stem rust, and strip rust can affect yield quality and quantity for a studied area. In addition, manual wheat disease identification and interpretation is time-consuming and cumbersome. Currently, decisions related to plants mainly rely on the level of expertise in the domain. To resolve these challenges and to identify wheat disease as early as possible, we implemented different deep learning models such as In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Various ML, IP, CV, and DL methods were assessed for different types of crop diseases in simple and complex background images. A framework presented in [25] used prominent DL networks such as ResNet 50, InceptionV3, and VGG19. The researchers compared the results of all these networks on a single dataset contains 1500 images representing three types of leaf diseases.…”
Section: Background Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various ML, IP, CV, and DL methods were assessed for different types of crop diseases in simple and complex background images. A framework presented in [25] used prominent DL networks such as ResNet 50, InceptionV3, and VGG19. The researchers compared the results of all these networks on a single dataset contains 1500 images representing three types of leaf diseases.…”
Section: Background Studiesmentioning
confidence: 99%
“…From Figs. 7 and 8, it was observed that our proposed method outclassed the methods presented in [17][18][19][20][21][22][23][24][25][26] in all cases. Furthermore, the results achieved form comparative methods were severely degraded using busy background crop led acquired images.…”
mentioning
confidence: 95%
“…Jiang et al [72] developed a wheat disease identification system for seven CNN models. After applying retuning training tactics, performance improvement has been noticed.…”
Section: Survey Based On Wheat Leaf Diseasesmentioning
confidence: 99%
“…They have discovered that the accuracy rates are more than 90 percent for three main disorders (powdery mildew, leaf rust, and stripe rust). In [7], author developed a Computer Vision Framework for the Identification and Classification of Wheat Diseases Using Jetson GPU Infrastructure demonstrating that manually identifying and interpreting wheat illnesses requires a significant amount of time and effort. They demonstrated that the VGG19 model was accurate in identifying wheat disease 99.38% of the time.…”
Section: Literature Reviewmentioning
confidence: 99%